If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+10+4x=-53
We simplify the equation to the form, which is simple to understand
5x+10+4x=-53
We move all terms containing x to the left and all other terms to the right.
+5x+4x=-53-10
We simplify left and right side of the equation.
+9x=-63
We divide both sides of the equation by 9 to get x.
x=-7
| x-(-5.60)=4.5 | | 9x-x= | | 2.5x=2(x+5) | | x-(-23)=35 | | 7x^2+47x+30=0 | | -7=6n-1 | | 2(n-2)=4 | | 7w+w= | | -2+x+5x=46 | | 7(3k-2)+5=6(2k-1)+24 | | 7y+3=6y-6 | | 6=-2(7-6) | | 23+32= | | -2-4(t-5)=-2(t+3) | | 260=23.86-s | | 4y+17=13 | | 7k^2-57k+8=0 | | 6x-4x+1=12+2x-11 | | -4y+4=-3y | | 2(2-x)=3(-8+2x)-9 | | 7x+3=-3+2x+16 | | 2(7-3(1-x))+9x=-2+2(6(x+1)-3x) | | 12*144= | | x^2-8+24x=30x+10 | | 5x+15-2x=-21 | | 8k=24 | | 16m+0.75=0.125 | | 3x-26=217 | | -5h-8=-11-2h | | y=33.3x+2 | | 3(4y+8)-4(y-6)= | | 2p+6=-4p-8 |